2006
DOI: 10.1210/jc.2005-2109
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Expression of the Adenosine A1 Receptor in Adipose Tissue of Obese Black and White Women

Abstract: These data suggest that inhibition of lipolysis by adenosine has the potential to be greater in obese AAW, and this could possibly be one explanation for the observation that obese AAW have more difficulty in losing weight than obese CAW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 38 publications
2
14
1
Order By: Relevance
“…Although several previous studies suggested that AA women exhibit low rates of adipocyte lipolysis that may contribute to their propensity toward obesity ( 11,22 ), our data in postmenopausal women, as well as our previously published study of premenopausal women, show that AA race is not associated with a lower rate of lipolysis. In fact, in postmenopausal women, we fi nd the opposite, higher lipolysis under physiologically relevant conditions (i.e., insulin-or PIA-suppressed).…”
Section: Discussioncontrasting
confidence: 65%
“…Although several previous studies suggested that AA women exhibit low rates of adipocyte lipolysis that may contribute to their propensity toward obesity ( 11,22 ), our data in postmenopausal women, as well as our previously published study of premenopausal women, show that AA race is not associated with a lower rate of lipolysis. In fact, in postmenopausal women, we fi nd the opposite, higher lipolysis under physiologically relevant conditions (i.e., insulin-or PIA-suppressed).…”
Section: Discussioncontrasting
confidence: 65%
“…LIPE is an enzyme with lipolytic properties and catalyzes the rate-limiting step of lipolysis by hydrolyzing the stored triacylglycerols and diacylglycerols into fatty acids and glycerol [41]. In our study, LIPE was significantly differentially down-regulated in EAT and MAT compared to SAT.…”
Section: Discussionsupporting
confidence: 47%
“…Why this was true for black girls and not white girls is not entirely clear, but may be related to a greater propensity toward overweight, higher rates of sedentary behaviors, 35 or differences in metabolic rate. 36,37 Our findings suggest that meal frequency may be a particularly important variable to consider when designing culturally specific obesity prevention and treatment programs.…”
Section: Discussionmentioning
confidence: 87%